Determining the Reasons of Older People for Choosing a Nursing Home: A Comparative Study - Yüksel, Arzu; Yilmaz, Emel Bahadir; Kesekci, Cansu Esra (Magyar Gerontológia, 2021)
Purpose: This study was conducted as a descriptive and comparative study to determine why a nursing home was chosen for the elderly. Methods: The population of the descriptive study consisted of older people living in a community-dwelling or a nursing home in the Central Anatolian Region of Turkey. The sample consisted of 342 elderly individuals who agreed to participate in the study between October and November 2019 (nursing home: n = 79, community-dwelling: n = 263). After obtaining the permission of the ethics committee (no: 2019/04-03), the data were collected by “Questionnaire Form for Individuals Living in Nursing Homes” and “Questionnaires for Individuals Living in Community-Dwelling." The Chi-square Test analyzed data, and the descriptive characteristics were presented as numbers, percentage, mean, standard deviation, minimum and maximum. Results: The average age of the elderly living in a nursing home was 77.35±7.40 (min: 66, max: 97), and the average age of community-dwelling older people was 70.90±5.57 (min: 65, max: 88). Before coming to the nursing home, 38.0% lived with their spouses, and 35.4% lived alone. 81.7% of community-dwelling older people lived with their families. There was a difference in terms of some sociodemographic variables between both groups. Elderly people staying in nursing home; 26.6% were in the 76-81 age group; 26.6% did not have children; 38.0% had no income; 16.5% had a physical disability; 82.3% used dentures; 13.9% couldn’t do their daily care; 22.8% had low self-confident; 62.0% had sleep problems; 67.1% had no social activity; 35.4% were smokers; 88.6% of them had not visited a nursing home before (p < 0.05). Conclusion: Compared to the community-dwelling older people, the elderly living in a nursing home were more senior, lonely, had a lower income, had higher physical disabilities, had lower social activity and self-confidence, had more sleep problems, and smoked.